The Profile and Content of Polyphenols and Carotenoids in Local and Commercial Sweet Cherry Fruits (Prunus avium L.) and Their Antioxidant Activity In Vitro - Dominika Średnicka-Tober; Alicja Ponder; Ewelina Hallmann; Agnieszka Głowacka; Elżbieta Rozpara (MDPI AG, 2019)
The aim of this study was to evaluate and compare the content of a number of bioactive compounds and antioxidant activity of fruits of selected local and commercial sweet cherry (Prunus avium L.) cultivars. The experiment showed that the selected cultivars of sweet cherries differ significantly in the content of polyphenolic compounds and carotenoids. The fruits of commercial sweet cherry cultivars were, on average, richer in polyphenols (the sum of phenolic compounds determined chromatographically), flavonoids, as well as anthocyanins and were characterized by higher antioxidant activity when compared to the local, traditional cultivars. In the group of the traditional sweet cherry cultivars, particular attention could be paid to Black Late cv., showing the highest antioxidant activity of fruits. In the group of commercial sweet cherry cultivars, Cordia and Sylvia fruits could be recognized as being rich in bioactive compounds with high antioxidant activity. Yellow skin cultivars were characterized by the highest concentrations of carotenoids. Strong positive correlations between the identified bioactive compounds and antioxidant activity of fruits were also found. Although different cultivars of sweet cherries show a high variability in phenolics and carotenoids profiles as well as in the antioxidant activity of fruits, they all should be, similarly to other types of cherries, recognized as a rich source of bioactive compounds with an antioxidant potential.